One currency, one price? Euro changeover-related inflation in Estonia - Jaanika Meriküll; Tairi R\~o\~om (European Central Bank (ECB), 2014)
This paper studies euro changeover-related inflation using disaggregated price level data. The difference-in-differences approach is used and the control group for the treatment country, Estonia, is built from 12 euro area countries. The Nielsen Company disaggregated price data are employed at product, brand and shop-type level. The results indicate that while the overall inflationary effect of euro adoption was modest, the effects were significantly different across various market segments. Changeover-related inflation was higher for products that were relatively cheaper than the euro area average. Inflationary effects were stronger in smaller shops.
Keywords: D49; P46; E58; 330; consumer behaviour; currency changeovers; euro; market concentration